Links Between Terrorism, Organized Crime and Crime: The Case of the Sahel Region. Issue 1 (10th September 2014) - Alda, Erik; Sala, Joseph L.
Many observers hold that terrorist groups and transnational criminal networks share many of the same characteristics, methods and tactics. There are many examples cited to demonstrate these observations are not coincidental, but indicative of a trend: a trend that is a growing threat to the security interests of many nations. We propose that the intersection of criminal networks and terrorist organizations can be broadly grouped into three categories – coexistence (they coincidentally occupy and operate in the same geographic space at the same time), cooperation (they decide that their mutual interests are both served, or at not least severely threatened, by temporarily working together) and convergence (each begins to engage in behavior(s) that is/are more commonly associated with the other). The activities of these types of organizations in the Sahel region of Africa provide examples of all three categories of interactions. This perceived threat has prompted action and policy choices by a number of actors in the sub-region. But this assessment might not be accurate and may, in fact, be an attempt to force an extra-regional, inappropriate paradigm upon a specific situation and set of circumstances where they do not apply.